Radio frequency energy harvesting from a feeding source in a passive deep brain stimulation device for murine preclinical research. Issue 10 (October 2015) - Hosain, Md Kamal; Kouzani, Abbas Z.; Tye, Susannah J.; Samad, Mst Fateha; Kale, Rajas P.; Bennet, Kevin E.; Manciu, Felicia S.; Berk, Michael
Abstract This paper presents the development of an energy harvesting circuit for use with a head-mountable deep brain stimulation (DBS) device. It consists of a circular planar inverted-F antenna (PIFA) and a Schottky diode-based Cockcroft-Walton 4-voltage rectifier. The PIFA has the volume of π × 102 × 1.5 mm3, resonance frequency of 915 MHz, and bandwidth of 16 MHz (909–925 MHz) at a return loss of −10 dB. The rectifier offers maximum efficiency of 78% for the input power of −5 dBm at a 5 kΩ load resistance. The developed rectenna operates efficiently at 915 MHz for the input power within −15 dBm to +5 dBm. For operating a DBS device, the DC voltage of 2 V is recorded from the rectenna terminal at a distance of 55 cm away from a 26.77 dBm transmitter in free space. An in-vitro test of the DBS device is presented.